MODEL PREDIKSI FAKTOR RISIKO INFEKSI TB PARU KONTAK SERUMAH UNTUK PERENCANAAN PROGRAM DI KABUPATEN OKU PROVINSI SUMATERA SELATAN TAHUN 2010 - Ekowati Retnaningsih; Yulian Taviv; Yahya Yahya (Publikasi Penelitian Terapan dan Kebijakan, 2020)
This study aims to obtain TB infection predictive model of home contact in OKU district of South Sumatra Province in 2010. Research design used cross sectional design with quantitative paradigm. Population of the study were all family members that living with TB patient in one home. Quota sampling was carried out in accordance with the number of respondents who are capable of reaching 100 persons. The Result of this study was the prevalence of a family who contact with pulmonary tuberculosis patients are 80%. The probability that someone at risk of TB infection is 0.94 if they are under nutrition, living in overcrowded homes, did not get TB exam and have a low education level (< SD).